GRAZING IN THE LAND ECOSYSTEMS OF INDIA - Whyte, R O (Annals of Arid Zone, 2016)
The situation that is rapidly becoming critical, whereby increasing human and livestock populations are competing for limited land resources. will lead to polarization in grassland and fodder research and field application. The future place of different types and intensities of animal husbandry in the land ecosystem is reviewed in relation to the prior demand for land for the production of food of adequate quality., for direct human consumption and for the vulnerable groups of the population.